Respuesta :
Answer:
x = -4
y = 4
Step-by-step explanation:
Subtract the two equations
be sure to take the minus sign through the whole bottom equation
the 6y's will cancel and you are left with 3x = -12 or x =-4
Then take the x= -4 and plug it back into the top equation to get y = 4
Answer:
(x,y) = (-4,4)
Step-by-step explanation:
7x + 6y = -4
6y = 8 - 4x
substitute the value of 6y into the equation
--------------------------
7x + 8 - 4x = -4
Solve
---------------------------
x = -4
substitute the value of x into the equation
---------------------------
6y = 8 - 4(-4)
solve
----------------------------
y = 4
therefore,
----------------------------
(x,y) = (-4,4)